Fenologia, produção e qualidade fisiológica de sementes de mini melancia cultivada com solução nutritiva salina - Alves, Tatianne Raianne Costa (2021)
The economically profitable production of the crop is related, among other factors, to the quality of the seeds, the production system and the water used in irrigation or preparation of nutrient solutions. The study was developed with the objective of evaluating the phenology, production and vigor of mini watermelon seeds irrigated with brackish water and different substrates. In the fruit and seed production phase, the experiment was conducted in a greenhouse and the treatments were distributed in subdivided plots, in a 5 x 2 factorial scheme, in a randomized block design (DBC) with four replications of two plants. The main portion was composed of five electrical conductivities of irrigation water, CEa (S1 = 0.5, S2 = 2.4, S3 = 4.0, S4 = 5.5 and S5 = 6.9 dS m-1) and the subplots were composed of two cultivation substrates (coconut fiber and sand). The phase of quantification of the physiological quality of the seeds was determined in the laboratory, in a completely randomized design, and the treatments were distributed in a 5 x 2 factorial scheme, referring to the seeds produced in the five electrical conductivities of the water, CEa (S1 = 0.5, S2 = 2.4, S3 = 4.0, S4 = 5.5 and S5 = 6.9 dS m-1) and two substrates (coconut fiber and sand), with four replications of 50 seeds. In the greenhouse experiment, days for flowering, days for fruit ripening, crop cycle, longitudinal and transversal diameters of the fruit, weight of the fruit, number and weight of seeds per fruit were evaluated. In the laboratory experiment, the percentage of germination and emergence, seed biometry, mass of 100 seeds, accelerated aging test and electrical conductivity were analyzed. The hydroponic cultivation of mini watermelon (cv. Sugar Baby) nourished with a solution containing high salinity water slows growth, anticipates the crop cycle and reduces the production of mini watermelon fruits. The viability and vigor of watermelon seeds are not affected when brackish water is used in the hydroponic nutrient solution with up to 6.9 ds m-1. The coconut fiber substrate is the most suitable for producing mini watermelons in hydroponic cultivation when using water brackish to prepare the nutrient solution